1989
DOI: 10.1002/hep.1840090305
|View full text |Cite
|
Sign up to set email alerts
|

Localization of ammonia-metabolizing enzymes in human liver: Ontogenesis of heterogeneity

Abstract: Immunohistochemical analysis of human liver (8 to 94 years) shows a compartmentation of ammonia-metabolizing enzymes across the acinus. The highest concentration of carbamoylphosphate synthetase (ammonia) is found in the parenchymal cells around the terminal portal venules. Glutamine synthetase is found in a small pericentral compartment two to three cells thick. In contrast to observations in rat liver, in human liver a well-recognizable intermediate zone can be distinguished in which neither enzyme can be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 21 publications
1
50
0
3
Order By: Relevance
“…GS mRNA, as well as ALB mRNA, was detected in 9 of 10 samples from different donors, CK-18 mRNA was detected in 4 of 10 samples, and AFP mRNA was seen in 2 of 10 samples. GS is known to be expressed in mature hepatocytes [19,20], CK-18 is expressed in the hepatocyte lineage [21,22], and AFP is expressed in hepatic progenitor cells, including oval cells [23,24]. These previous reports support our findings that the cultured cells had the same characteristics as the hepatocyte lineage.…”
Section: Expression Profiles Of Hepatocyte Lineage Markerssupporting
confidence: 88%
“…GS mRNA, as well as ALB mRNA, was detected in 9 of 10 samples from different donors, CK-18 mRNA was detected in 4 of 10 samples, and AFP mRNA was seen in 2 of 10 samples. GS is known to be expressed in mature hepatocytes [19,20], CK-18 is expressed in the hepatocyte lineage [21,22], and AFP is expressed in hepatic progenitor cells, including oval cells [23,24]. These previous reports support our findings that the cultured cells had the same characteristics as the hepatocyte lineage.…”
Section: Expression Profiles Of Hepatocyte Lineage Markerssupporting
confidence: 88%
“…50 It is known that glutamine, the end product of GS activity, is the major energy source of tumor cells. 51 Most importantly, GS is a target gene of ␤-catenin so that its overexpression is associated with mutations of ␤-catenin or with activation of this pathway. [52][53][54] Up-regulation of GS messenger RNA, protein, and activity were shown by Christa et al 52 in human HCC, while Osada et al 55 reported the stepwise increase in GS immunoreactivity from precancerous lesions to early HCC to progressed HCC.…”
Section: Emerging Tumor Markersmentioning
confidence: 99%
“…(42) Accordingly, periportal hepatocytes are well equipped to take up and metabolize glutamine (4,27) because they express the glutamine transporter SLC38A5, (35) glutaminase-2 (EC 3.5.1.2), (43,44) and all enzymes of the urea cycle. (45,46) The trans-membranous Na 1 gradient mediates the uptake of >70% of plasma glutamine and causes it to accumulate intracellularly to 3-5 mmol/ kg. (35,47) A further pH-dependent 4-fold to 5-fold concentrative transport of glutamine occurs across the mitochondrial membrane (47,48) to accommodate the relatively high Michaelis constant of glutaminase-2 in situ (6 mmol/L).…”
Section: Periportal Hepatocytes Catabolize Glutaminementioning
confidence: 99%